(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2018)
The main goal of the present study was to identify the possible variables that affect women staying in abusive relationships. It is known that more than half of the women who already have suffered some type of violence did not report their aggressors, and most of them stayed in the relationship. To investigate this reality, a field work was conducted through semi-directed interview with three women victims of domestic violence. The behavior-analytic approach was used to analyze and understand this context. Results identified contingencies for staying in the abusive relationship, such as: hope for behavior change from the partner, financial and emotional dependence, concerns about raising children, lack of support, and passivity.